Collected maxims and other reflections - La Rochefoucauld, François. (Oxford Oxford University Press, 2007)
Deceptively brief and insidiously easy to read, La Rochefoucauld's shrewd, unflattering analyses of human behavior have influenced writers, thinkers, and public figures as various as Voltaire, Proust, de Gaulle, Nietzsche, and Conan Doyle. This is the fullest collection of La Rochefoucauld's writings ever published in English, and includes the first complete translation of the Rf̌lexions diverses (Miscellaneous Reflections). This edition includes an excellent introduction that surveys La Rochefoucauld's life, the genesis of his work, its form and content, and its influence, as well as comprehensive explanatory notes. A table of alternative maxim numbers and an extensive and invaluable index of topics help the reader to locate any maxim quickly and to appreciate the full range of La Rochefoucauld's thought on any of his favorite themes, such as self-love, vice and virtue, love and jealousy, friendship and self-interest, passion and pride.
Includes bibliographical references (p. [xl]-xli ) and index.